DESAIN STRUKTUR SHELTER INOVATIF SEBAGAI TEMPAT EVAKUASI SEMENTARA DI BANYUWANGI - Ade Fani S. I.; Mirza Ghulam Rifqi; Zulis Erwanto; M. Shofi’ul Amin (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
In 1994 the tsunami in Banyuwangi affected 4 regions namely Pancer, Lampon, Rajegwesi, Grajagan with an earthquake magnitude of 7.5, this requires that disaster-prone areas in Banyuwangi must have an evacuation infrastructure for natural disasters and emergency plans. This study aims to plan an innovative shelter structure design based on temporary evacuation sites in Banyuwangi. The planning used in designing this shelter is to review the structure of columns, beams, plates, and raft foundations, the design of the structure used is steel structure made following the provisions of the load and durability factor design (DFBK) using computer applications that refer to SNI 03- 1726-2019, SNI 03-1729-2015, SNI 03-1727-2013, and FEMA P646A. Based on the planning results, an innovative shelter with dimensions of 16 m x 4 m x 3.5 m, on the beam using IWF 350.350.19.19 steel profile and the column using IWF 350.350.19.19 with a weight of the shelter structure of 38292.9 Kg. The results of the beam structure planning with the control of flexural and shear interaction checks were 1.19 <1.375, the column structure planning with the control of the design compressive strength was 0.228 <1. The foundation of the raft is planned with dimensions of 16 m 4 m and it is recommended that the thickness is 80 cm with pressure control on the ground of 0.061 Kg/cm2 <0.188 Kg/cm2.